Surface modification of AMH-3 for development of mixed matrix membrane - Oh , P.C. (2016)
AMH-3 layered silicate is an attractive material for gas separation applications due to its 3D structure with crystallographic pore size of 3.4 Å. Nevertheless, AMH-3 is strongly hydrophilic due to the presence of cations between the silicate layers. Therefore, surface modification of AMH-3 is necessary in order to enhance its compatibility with hydrophobic polymer matrix of membranes. In this study, AMH-3 layered silicate was synthesized via hydrothermal synthesis method and functionalized with octyl(methyl)dimethyoxysilane to enhance its hydrophobicity, thereby improve adhesion and dispersion in mixed matrix membrane (MMM). The as-synthesized and functionalized AMH-3 were characterized with analytical tools such as FT-IR, XRD, SAP and contact angle. Functionalized AMH-3 showed higher surface area but reduced pore size. It also exhibited improved hydrophobicity compared to as-synthesized AMH-3. Flat sheet PSf/AMH-3 membranes were subsequently prepared by dry/wet phase inversion technique with varying AMH-3 loadings (1, 3 and 5 wt.%). As apparent from the thermogravimetric analysis, as-synthesized and functionalized AMH-3 showed no significant effect on the thermal stability and decomposition temperatures of the resultant MMMs. The synthesized membranes exhibited similar surface and cross-sectional morphologies with good distribution and dispersion of inorganic filler. Functionalized AMH-3 showed improved hydrophobicity, which results in enhanced compatibility and adhesion with the hydrophobic PSf polymer matrix.